(untitled) (Journal of history, 2026)
This article examines the process of reforming mektebs and madrasahs in the early 20th century as presented in the pages of Tatar newspapers. In the context of Jadidist reforms, the issue of preserving madrasahs as a stronghold of national spirit and Islam was crucial for Tatar society. Against the backdrop of increased governmental control over new-method schools, the "school question" emerged, for which the periodical press became a means of resolution. Discussions were held in its pages, appeals were made to government institutions, and calls were issued to the people to support the cause. The unique collection of articles compiled by N.F. Katanov, primarily from the Tatar newspaper Koyash, provided an opportunity to view the problems of reforming Muslim schools from a new perspective. The reforms led to the weakening of madrasahs, prompting a struggle for their preservation. Based on this material, the study aims to analyze the state of Muslim educational institutions during the post-reform period, the situation surrounding them from the authorities’ perspective, and the formation of a flexible mechanism for their modernization and preservation by Tatar society under the strict control of the Tsarist government. In working on this article, methods of analyzing the historical process based on the principle of historicism were employed. The method of comparison was used to study the formation of the Tatar periodical press and to determine the direction of discussions. In conclusion, it is argued that the "school question" was not merely about deciding the future of madrasahs. It expressed the desire of the Turkic-Muslim population of the Russian Empire for national awakening.